(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sektiana SP, Abdillah AA, Alam JM, Isroni W, Dewi NM, Kim HW, Androyono S. 2022. Diversity of the Tabuhan Island coral reef fish revealed by DNA barcoding and implication on conservation strategy in Banyuwangi, Indonesia. Biodiversitas 23: 4844-4851. Tabuhan Island, Banyuwangi, Indonesia, is one of the mainstays of coastal tourism with the charm of coral reefs and has a fairly high potential for reef fish diversity. Coral reef ecosystems provide suitable habitats for reef fish to spawning ground, feeding ground, and nursery ground which provide suitable nurturing areas. Here, studies have been carried out on the diversity of reef fish by molecular approaches. The molecular identification approach provides accuracy in identification to the species level. In this study, samples of reef fish species from Tabuhan Island waters were identified molecularly in the mitochondrial DNA region of the cytochrome c oxidase subunit I (COI). The identification results showed that 53 specimens had been identified, and some of the themes were registered in the GenBank database to strengthen the genetic information of reef fish in the tropical region of Indonesia. A total of 53 specimens were identified, spread over 49 species, 3 orders, and 17 families dominated by reef fish groups from Labridae (20 species). The phylogenetic tree reconstruction shows that the family collects several species, but some species are classified as paraphyletic. The results of this molecular identification have also succeeded in registering 35 COI sequences in the Genbank database. The mtDNA sequence data is very important and becomes the basis for the genetic conservation resources in coral reef ecosystems.